2008
DOI: 10.1007/s11103-008-9445-y
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a novel CBL-interacting protein kinase from maize

Abstract: A novel CBL-interacting protein kinase (CIPK) gene, ZmCIPK16, was isolated from maize (Zea mays), which has been certified to have two copies in the genome. The ZmCIPK16 is strongly induced in maize seedlings by PEG, NaCl, ABA, dehydration, heat and drought, but not by cold. A yeast two-hybrid assay demonstrated that ZmCIPK16 interacted with ZmCBL3, ZmCBL4, ZmCBL5, and ZmCBL8. Bimolecular fluorescence complementation (BiFC) assays prove that ZmCIPK16 can interact with ZmCBL3, ZmCBL4, ZmCBL5, and ZmCBL8 in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 49 publications
4
52
0
1
Order By: Relevance
“…Subsequent studies have demonstrated the functional conservation of the CBL-CIPK pathway in Populus (Yu et al, 2007), grape (Weinl and Kudla, 2009), sorghum (Li et al, 2010), and maize (Chen et al, 2011). Enhanced tolerance to diverse stresses has also been regularly observed in transgenic Arabidopsis because of the overexpression of CIPKs (Zhao et al, 2009;Chen et al, 2012), rice (Xiang et al, 2007), tomato Huertas et al, 2012), tobacco (Tripathi et al, 2009), and apple (Hu et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Subsequent studies have demonstrated the functional conservation of the CBL-CIPK pathway in Populus (Yu et al, 2007), grape (Weinl and Kudla, 2009), sorghum (Li et al, 2010), and maize (Chen et al, 2011). Enhanced tolerance to diverse stresses has also been regularly observed in transgenic Arabidopsis because of the overexpression of CIPKs (Zhao et al, 2009;Chen et al, 2012), rice (Xiang et al, 2007), tomato Huertas et al, 2012), tobacco (Tripathi et al, 2009), and apple (Hu et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Remarkable progress has been made in determining the functions of CIPKs in response to abiotic stress in model plants and certain crops (Imamura et al, 2008;Zhao et al, 2009;Tai et al, 2013). For example, in Arabidopsis, CIPK1 and CIPK3 are crosstalk nodes between the ABA-dependent and ABA-independent pathways under environmental stress (Kim et al, 2003;D'Angelo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A few CIPKs have also been functionally characterized by gain-of-function approach in crop plants such as rice (Oryza sativa), pea (Pisum sativum), and maize (Zea mays) and were found to be involved in osmotic stress responses (Mahajan et al, 2006;Xiang et al, 2007;Yang et al, 2008;Tripathi et al, 2009;Zhao et al, 2009;Cuéllar et al, 2010).…”
mentioning
confidence: 99%
“…5.2 ; Kim et al 2007 ;Waadt et al 2008 ;Ren et al 2013 ). Conservation of the SOS pathway has been reported in rice, Brassica juncea , maize, tomato, Populus trichocarpa , Populus euphratica , and apple (Martínez-Atienza et al 2007 ;Wang et al 2007Wang et al , 2012aKumar et al 2009 ;Zhao et al 2009 ;Kushwaha et al 2011 ;Hu et al 2012 ;Tang et al 2010 ;Lv et al 2014 ;Oh et al 2008 ). From monocots like rice and wheat, using reverse functional genetic tool such as gain/loss of function of OsCIPK3, OsCIPK12, OsCIPK15, OsCIPK23, OsCIPK31, and TaCIPK14 has been demonstrated to be intricately involved in diverse abiotic stress pathways, namely, cold, salt, PEG, ABA, ethylene, and H 2 O 2 (Xiang et al 2007 ;Yang et al 2008 ;Piao et al 2010 ;Deng et al 2013a ).…”
Section: Oscbl8mentioning
confidence: 99%
“…However, specifi c localization was not apparent for OsCBL1 . In maize, ZmCIPK16 was found to be distributed in the nucleus, plasma membrane, and cytoplasm; however, its interacting partners ZmCBL3, ZmCBL4, and ZmCBL5 localized in the plasma membrane (Zhao et al 2009 ); in canola BnaCBL1 protein localized in nuclei and plasma membrane of leaf epidermal cells. BnaCBL9 and BnaCBL3 localized in the cytoplasm and nuclei, whereas BnaCBL10 was found to be located on tonoplast along with cytoplasm and nucleus ).…”
Section: Subcellular Proteomics and Functional Relevancementioning
confidence: 99%